2009
DOI: 10.1183/09031936.50075408
|View full text |Cite
|
Sign up to set email alerts
|

Serum adipocyte-fatty acid binding protein level is elevated in severe OSA and correlates with insulin resistance

Abstract: Obstructive sleep apnoea (OSA) is associated with insulin resistance and metabolic syndrome. There is evidence that adipocyte-fatty acid binding protein (A-FABP) may be involved in the development of cardiometabolic dysfunction. The present authors hypothesise that A-FABP is upregulated in OSA.A total of 124 males without hypertension, diabetes mellitus, hyperlipidaemia or cardiovascular disease were recruited and underwent polysomnography. Serum A-FABP levels showed significant positive correlations with dura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
17
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
6
17
1
Order By: Relevance
“…In OSAS patients without MS, FFA levels were also higher in the severe group than in mild-to-moderate group. Our results are concordant with a study by LAM et al [29]. Those authors found that adipocyte fatty acid-binding protein levels correlated with obstructive sleep apnoea independently of obesity [29].…”
Section: Sleep-related Disorderssupporting
confidence: 94%
See 1 more Smart Citation
“…In OSAS patients without MS, FFA levels were also higher in the severe group than in mild-to-moderate group. Our results are concordant with a study by LAM et al [29]. Those authors found that adipocyte fatty acid-binding protein levels correlated with obstructive sleep apnoea independently of obesity [29].…”
Section: Sleep-related Disorderssupporting
confidence: 94%
“…Our results are concordant with a study by LAM et al [29]. Those authors found that adipocyte fatty acid-binding protein levels correlated with obstructive sleep apnoea independently of obesity [29]. Multiple linear regression controlling for BMI, sex, age and the presence of MS confirmed an independent association between AHI and FFA levels.…”
Section: Sleep-related Disorderssupporting
confidence: 93%
“…Although the physical mass is static, the composites of adiposity might have changed at the molecular levels after treatment. A number of inflammatory and neurohumoral mediators are produced from the adipose tissues, especially from the visceral adipose tissues which have been demonstrated to be involved in the pathogenesis of insulin resistance [33,36]. With the application of nCPAP treatment in the obese apnoeic group, the changes of these mediators and, hence, insulin sensitivity might have been more pronounced than the nonobese apnoeic group.…”
Section: Sleep-related Disordersmentioning
confidence: 99%
“…A positive correlation has been found between the level of A-FABP, level of fasting insulin and insulin resistance index [5]. Patients with rare haploinsufficiency of the gene for A-FABP have significantly reduced risk for diabetes and CVD [6].…”
Section: Introductionmentioning
confidence: 88%